The Effects of Digital Amnesia on Knowledge Construction and Memory Retention - Musa, Nazaruddin; Mukhtaruddin; Bakkara, Viona Febiyola (Khizanah al-Hikmah : Jurnal Ilmu Perpustakaan, Informasi, dan Kearsipan, 2023)
The growing usage of digital technologies raised concerns regarding the possible adverse effects of digital amnesia, in which people forget readily available knowledge saved in their gadgets. This study investigated the effects of digital amnesia on memory retention and knowledge construction through experiment studies. The tasks given to the participants required either digital devices or more conventional memory storage and retrieval methods. Memory performance and knowledge construction were assessed through various tests and assessments. The findings indicated that excessive reliance on digital devices for information storage led to digital amnesia. Participants who used digital tools exhibited lower memory retention and shallower information processing compared to those employing traditional memory strategies. The results highlighted the negative implications of digital amnesia for memory retention and knowledge construction. Striking a balance between reliance on digital tools and active engagement in memory processes was crucial. Actively encoding and retrieving information can mitigate risks associated with shallow processing and information overload.